Penggunaan Media Permainan “Spelling Bee” Untuk Meningkatkan Keterampilan Menulis Bahasa Arab - Chairani Astina; Toyibah Toyibah (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2020)
His study aims to determine: (1) The use of the spelling bee game media to improve the Arabic writing skills of the seventh grade students of MTs Bani Haji Abdul Rosyid Ngadirejo, (2) The difference in the improvement in the learning outcomes of students' Arabic writing skills using the spelling bee game media and the students who uses the lecture method in learning Arabic writing skills in class VII MTs Bani Haji Abdul Rosyid Ngadirejo. This research is a type of field research using a quantitative approach carried out at MTs Bani Haji Abdul Rosyid Ngadirejo, with the type of experimental research, while the research design is quasi experiment tqwo groups (experimental class and control class), which is a form of development of true experimental design which This design has a control group but does not fully function to control external variables that affect the implementation of the experiment. In this study, there are two variables, namely the independent variable and the dependent variable. The independent variable is the use of the spelling bee game media. And the dependent variable is the increase in Arabic writing skills of class VII students of MTs Bani Haji Abdul Rosyid Ngadirejo. The method of data collection is done by observation, interview, documentation and test methods. The results of this study indicate: 1) There was an increase in learning outcomes in the Arabic writing skills of the experimental class students by 0.345 and in the medium category. 2) The results of hypothesis testing show an error level of 1% with dk = n1 + n2-2 = 20 + 22-2 = 40 obtained t table = 2, 704. And for the error level of 5% with a value of dk = n1 + n2 - 2 = 20 + 22 - 2 = 40 obtained t table = 2.021. These results indicate that t count is greater than t table. The conclusion is that there are differences in the Arabic writing skills of grade VII students of MTs Bani Haji Abdul Rosyid Ngadirejo who use the spelling bee game media with the lecture method.